(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Hypoglycemic effects was observed with Spirulina (Spirulinaplatensis) when given as leaf extract in normal and alloxan diabetic rat. In this study 150 rats were included and divided into three groups of ten rats in each group. First group was normal control (A), Second group was diabetic control (B), third group was diabetic with Spirulina treated (C). The rats were treated with aqueous extract of Spirulina at a dose rate of 20 mg/kg body weight respectively for 3 weeks. During experimental period, day 0, day 7, day 14 and day 21 blood samples were collected from all groups and determined their blood sugar level using diabetic kit. The blood glucose levels were reduced from 165.5±10.65 mg/dL to 158.17±5.49 mg/dL in group C after 3 weeks treatment. On the other hand the average body weight were increased from 255.67±7.35 g to 286.17±8.56 g in group C after 3 weeks treatment. From the findings it is concluded that the Spirulina can be used as anti-diabetogenic agent in food. Res. Agric., Livest. Fish.7(3): 475-479, December 2020